Leadership of Madrasah Head in Improving the Quality Of Teachers in MTs Negeri 2 Deli Serdang - Riduan Riduan; Salman alfarisi (STAI Miftahul Ula Nganjuk, 2022)
The objectives to be achieved in this study are : To find out how the leadership role of the head of the madrasa in improving the quality of teachers in MTs Negeri 2 Deli Serdang. The type of research used by researchers is qualitative research with this type of research is expected to obtain a deep understanding and interpretation of the meaning of reality and facts that are relevant to the data in the field. The result of this research are: 1) The role that a madrasa head can play in his efforts to realize the goal is to improve quality by making himself a madrasa head who can position himself as an innovator, administrator, and motivator. 2) As the head of the madrasa in the implementation of leadership in improvingthe competence of his teachers, it is :p, especially by supervisingthe activities of teachers, both of which seek to hold training, finally by providing motivation directly or indirectly